Factors affecting univerasal life insurance investment intention: A consumer behavior theory perspective in the pre-pandemic era - Abuan, Roxanne Gail P. (Animo Repository, 2024)
The Philippines boasts a thriving stock market with over a million investors, predominantly local and increasingly utilizing online platforms, especially among those aged 18 to 44. In stark contrast, insurance penetration in 2018 was less than 1.2%, divided into life insurance, health insurance, and micro-insurance. The life insurance sector experienced significant growth, particularly in Variable Universal Life (VUL) insurance. This study delves into VUL, a unique insurance product blending a death benefit with investment components, akin to Unit Investment Trust Funds and Mutual funds. Despite substantial growth, 82% of adults lack comprehensive insurance coverage, citing various reasons. Consequently, the study explores factors influencing VUL purchase intentions among existing investors, bridging the gap between stock market and insurance investments. The literature review establishes the significance of perceived risk attitude, uncertainty, and product knowledge in investment decisions. It also explores the impact of cultural factors, product involvement, attitudes, and self-efficacy on investment intentions. The theoretical framework adopts the stimulus-response model, delving into environmental and perceptual dimensions to understand the factors shaping purchase intentions. Objectives and hypotheses are formulated, focusing on understanding and explaining the impact of factors on VUL purchase intentions. Methodologically, a descriptive-quantitative approach is employed, utilizing a convenience sampling technique. A questionnaire, refined through pre-screening, is disseminated through social media channels, targeting existing stock market and structured retail product investors without insurance. Data collection during Quarter 3 and Quarter 4 of 2019 resulted in 396 respondents, mostly undecided on certain factors, providing a nuanced understanding of their investment intentions. Confirmatory Factor Analysis validates construct reliability, with Cronbach's alpha exceeding 0.70. Correlation and structural equation modeling offer insights into relationships, despite model fit concerns. While supporting existing findings on risk attitude and product involvement, the study contradicts some literature regarding uncertainty, uncertainty avoidance, product knowledge, and self-efficacy. Recommendations include refining the measurement model, exploring indecision factors, longitudinal analyses, stakeholder consultation, and investigating contradictory findings. Practical implications emphasize translating research for financial institutions and continuous model evaluation. Overall, the study contributes to the understanding of investor behavior, specifically in the context of VUL purchase intentions, and provides a foundation for future research and practical applications.